2021
DOI: 10.1002/htj.22276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonlinear thermal radiation on unsteady MHD flow of Maxwell nanoliquid over a porous vertical sheet with chemical reaction

Abstract: The aim of the current article is to explore the impact of chemical reactions on magnetohydrodynamic mixed convective flow comprising Maxwell nanomaterial over a vertical porous surface with a convectively heated stretched surface. Heat transfers are also accounted for through thermal radiation. The modeled equations are formulated and transmuted into highly nonlinear partial differential equations into ordinary differential equations through suitable alteration, which is settled numerically through the Runge–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…Ali et al [18] looked at the physical efects of a stretched sheet with convective heating and a Cross fuid containing carboxymethyl cellulose. Similar research studies have been performed by several authors [19][20][21][22][23].…”
Section: Introductionsupporting
confidence: 82%
“…Ali et al [18] looked at the physical efects of a stretched sheet with convective heating and a Cross fuid containing carboxymethyl cellulose. Similar research studies have been performed by several authors [19][20][21][22][23].…”
Section: Introductionsupporting
confidence: 82%
“…We checked the accuracy of current outcomes with previous literature in the limited case and obtained a fantastic agreement. Table 1 displays a comparison of numeric outcome for Sherwood number various values of the thermal diffusion parameter with the published result of Farhan Ali et al, [23] with an outstanding agreement.…”
Section: Code Validationsupporting
confidence: 58%
“…Shatey [22] investigated the boundary layer flow of a Maxwell fluid past a vertical stretching sheet under the influence of thermophoresis and chemical reaction. Recently, Farhal Ali et al, [23] Multi-specific applications, including Arrhenius energy activation and species response, have been of great interest to scientists and researchers in oil supplies, in particular oil and chemical engineering, cooling reactors, geothermal engineering, material degradation, mechanical chemistry, and oil and water emulsions. Generally, the relationship between mass transfer and chemical reactions is very complex and can often be studied at different rates for fluid flow and mass transfer together, through the manufacture and digestion of reagent species.…”
Section: Introductionmentioning
confidence: 99%
“…Raza et al 21 performed research on the peristaltic transport of magnetohydrodynamic liquid in a porous duct with various carbon nanotubes. The influence of uneven thermal radiation on the boundary layer flow of unsteady Maxwell nanofluid past a vertical surface was discovered by Ali et al 22 Asha and Vijaylaxmi 23 investigated the impacts of thermal jump and inclined magnetic field on the peristaltic transport of Jeffrey fluid containing silver nanoparticles in the eccentric annuls under the long wavelength and low Reynolds number assumption. They concluded that temperature distribution is an enhancing function of radiation parameters.…”
Section: Introductionmentioning
confidence: 99%